IT taxation in Ukraine - Frolova, N. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2022)
The proceedings are devoted to the issue of tax policv response to the challenges of war and post-war periods in the case of Ukraine in terms of taxation of IT industrv. The current tendencies of fiscal revenues as well as cash and non-cash transactions in Ukraine are analvzed. Special tax regimes for IT industrv in Ukraine and worldwide are presented.
Keywords: Digital Service Tax; IT companies; Single Tax; Diia citу